2022
DOI: 10.20525/ijrbs.v11i2.1591
|View full text |Cite
|
Sign up to set email alerts
|

What do strategic responses achieve?

Abstract: This study purposed to investigate the effect of strategic responses on performance.  The study adopted a descriptive research design. The target population for the study was 3834 employees drawn from four telecommunication firms in Kenya. Proportionate stratified random sampling was used to select the sample size of 385 respondents. The study findings indicated that (i) research and development, technology advancement, and strategic training all had a significant positive effect on firm performance; (ii) tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Training employees to use new technologies is crucial for organizational success, as highlighted by research emphasizing the positive effects of strategic training on employee performance and innovation (Oketch & Muathe, 2022). Additionally, the integration of technology training has been shown to improve employees' acceptance and readiness for using mandated technology systems (Marler et al, 2006).…”
Section: Types Of Technology Used In Employee Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Training employees to use new technologies is crucial for organizational success, as highlighted by research emphasizing the positive effects of strategic training on employee performance and innovation (Oketch & Muathe, 2022). Additionally, the integration of technology training has been shown to improve employees' acceptance and readiness for using mandated technology systems (Marler et al, 2006).…”
Section: Types Of Technology Used In Employee Trainingmentioning
confidence: 99%
“…In the context of employee training, the application of technology can face several limitations. One key limitation is the need for employees to be well-trained to effectively utilize new technologies for innovation and productivity (Oketch & Muathe, 2022). Additionally, the trap of path dependency can hinder the optimal utilization of firm-specific technological knowledge, emphasizing the importance of continuous training for R&D employees to enhance productivity (Kim & Lee, 2021).…”
Section: Possible Limitations In the Application Of Technology In The...mentioning
confidence: 99%
“…A study by Oketch and Muathe (2022) also noted that most of the telecommunication companies in Kenya were constantly downsizing their operations and reducing the number of employees as a way of saving costs, amid decline in revenues and profitability. Ngugi and Murugi (2022) on the other hand reported that despite the promising future in the Kenyan telecommunication industry, the sector was crippled with reduced customer satisfaction, poor market coverage and increased operational costs.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…MIS capabilities in the manufacturing industry in Kenya have largely contributed to improved productivity and profitability of firms when integrated in daily operations (Oketch & Muathe, 2022). According to Owino & Waema (2020), Kenya's high speed internet connection together with the availability of information technology devices like the mobile phones have facilitated the quick adoption of technology in running businesses which has expanded the market reach and at the same time improved on productivity and profitability of businesses.…”
Section: Introductionmentioning
confidence: 99%